Oral health of adults with intellectual disabilities: a systematic review. Issue 11 (23rd May 2019) - Ward, L. M.; Cooper, S. A.; Hughes‐McCormack, L.; Macpherson, L.; Kinnear, D.
Abstract: Background: There have been several past reports that adults with intellectual disabilities experience poor oral health (tooth loss, periodontal health and untreated dental caries). Loss of a functional dentition has serious consequences, including problems with chewing, swallowing, nutrition, speech, temporomandibular joint osteoarthritis and pain and systemic health conditions. Poor oral health is largely preventable through proactive oral care support. In recent years, social care provision for adults has changed, with deinstitutionalisation and home‐based personalised care now being the typical provision in high income countries. Hence, oral health inequalities might be reducing. However, there is limited recent evidence‐synthesis on the topic. We aimed to address this. Method: PROSPERO registration number: CRD42018089880. We conducted a preferred reporting items for systematic reviews and meta‐analyses systematic review of publications since 2008. Four databases were searched with a clear search strategy, strict inclusion criteria for selection of papers, double scoring (two raters), systematic data extraction and quality appraisal of included papers. Results: A total of 33/3958 retrieved articles were included, of which 14 were drawn from dental service users and 10 from Special Olympic athletes, therefore not necessarily being representative of the wider population with intellectual disabilities. Despite this limitation, adults with intellectual disabilities were still shown to experience poor oral health. High levels of poor oral hygiene and gingivitis were found, with many also affected by periodontitis and untreated dental decay. There is clear unmet need relating to both periodontal (gum) and tooth health, leading to tooth loss. Conclusions: Despite reports in the past of poor oral health amongst adults with intellectual disabilities, and despite it being preventable, there remains a high burden of poor oral health. This highlights the need to raise awareness, and for polices on effective daily oral care, and appropriate service provision. The importance of oral health and its possible negative sequelae needs to be elevated amongst carers and professionals.